Literatura surda nas práticas de professores surdos em escola bilíngue - Queiroz, Alicyary Moreira (2021)
This dissertation was carried out by a deaf researcher and has as its focus the contextualization of deaf teachers in Bilingual Schools, concerning the pedagogical practice of storytelling. It is a critical and necessary reflection about curriculum´s embracement of Deaf Culture in the area of Deaf Literature and Sign Language, using dynamics with deaf children and investigating the adaptation of specific literature in Sign Language by Deaf Teachers. This study has as theoretical basis authors who approach the socio-anthropological view of the Deaf Being as subjects, and professionally, with Deaf Teachers active in the deaf community. The aim is to analyze the articulations between the knowledge of Deaf Literature, the use of Sign Language and the curriculum, thus identifying its conceptions and implications through Deaf Teachers who use storytelling strategies in their pedagogical practices. Through a qualitative methodology, the field research was developed from interviews with four Deaf Teachers who work in a Bilingual School. The aim was to understand their practices, their critical position, if they realize the importance of an elaborated curriculum in teaching, which considers the relation with Sign Language Literature